Studies on the role of HAP4, MIG1 and MIG2 in transcriptional control network of Saccharomyces Cerevisiae - Dereli, Elif. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In this study, transcriptional responses of HAP4, MIG1, MIG2 and GSM genes to transient perturbations under glucose and nitrogen limited conditions were investigated in order to understand glucose sensing and signaling pathways in yeast. For this purpose six sets of chemostat experiments with pulse injections were performed with three homozygous deletion strains (ho /ho , mig1 /mig1 and mig2 /mig2 ) of Saccharomyces cerevisiae BY4743. Growth characteristics and metabolite profiles for glucose, ethanol, ammonia and glycerol were compared. mig1 /mig1 and mig2 /mig2 strains produced higher biomass than ho /ho under glucose limitation. Absence of MIG2 did not affect the glucose repression mechanism as much as MIG1. mig2 /mig2 produced the lowest biomass under nitrogen limitation. The glucose concentration was the highest in ho /ho in nitrogen limited chemostat cultivation. The expression profiles of HAP4, MIG1, MIG2 and GSM1 were determined via real time rt-qPCR. HAP4, MIG1, MIG2 and GSM1 were up-regulated under glucose limitation in ho /ho . Deletion of MIG1 or MIG2 resulted in repression of HAP4 and GSM1 under glucose limitation. After the glucose pulse injection GSM1 was activated after HAP4 in mig1 /mig1 and this provided further evidence that GSM1 is regulated by HAP complex. GSM1 showed similar expression levels with HAP4 both in ho /ho and mig2 /mig2 throughout the glucose limited cultivations. This indicated a possible role of GSM1 in regulation of respiratory pathway of yeast together with HAP4. Deletion of MIG1 diminished the up-regulation of MIG2 under nitrogen limitation.
Keywords: Saccharomyces cerevisiae.; Genetic transcription.; Transcription factors.